PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP PENINGKATAN EMPATI SISWA KELAS X SMAN 4 PEKANBARU TP. 2014/2015 - Pitri Ramani Ramani; Raja Arlizon Arlizon; Abu Asyari Asyari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The title of this research is "group guidance services effect on the improvement of empathy of student class x sman 4 pekanbaru tp. 2014/2015 ". This study aims 1) To know the description of empathy of studenst class X SMAN 4 Pekanbaru before given group guidance services. 2) To know the process of implementation of group guidance services to increase empathy class X SMAN 4 Pekanbaru. 3) To know the description of empathy of students class X SMAN 4 Pekanbaru after given group guidance services. 4) To determine differences in empathy of studenst class X of SMAN 4 Pekanbaru before and after given group guidance services. 5) To determine how much influence the group guidance services to increase empathy of studenst class X SMAN 4 Pekanbaru.Variable this study consisted of one variable with two variants, namely: 1. Empathy students before given group guidance services (X1). 2. Empathy students after given group guidance services (X2). Ways sampling using purposive sampling technique. The subjects were as many as 30 students. With the population of the entire class X SMAN 4 Pekanbaru TA 20142015. This study uses a Pre-Experiment with patterns of one-group pretest-posttest. Instrument in this study was a questionnaire empathy. This test consists of 27 items of empathy with alternative "yes" and "no" and then the data is processed with statistics. The hypothesis proposed that there is a significant difference to the students before the increase in empathy after the given group guidance services. From the results of research conducted, with using t test obtained t of -6.96 and ttable of 2,000. So, thitung> ttable (6.96> 2.000). So Ho rejected and Ha accepted, which means that in this study there are significant differences to increase in empathy with the students before after given group guidance services. From the calculation of product moment correlation r xy = 0.523, of coefficient of Determinant or r2 = 0,273 which means there is a 27.3% contribution to the improvement of guidance services group empathy class X of SMAN 4 Pekanbaru TA 2014/2015.Key words: Guidance Group, Empathy